Differences in Entrepreneurial Abilities from the Gender Perspective among Students at the Engineering Faculty of the Universidad Cooperativa de Colombia - Becerra Arias, Luis Abraham (Ingeniería Solidaria, 2015)
This article is the product of the research work entitled “Study of the Profile of Entrepreneurs at the Bogotá campus of the Universidad Cooperativa de Colombia” (“Estudio de perfil del emprendedor de la Universidad Cooperativa de Colombia, sede Bogotá”). In 2012, the Induspymes research group analyzed perceptions about the development of entrepreneurialabilities among members of the academic and student community at the engineering faculty at the Bogotá campus, from the gender perspective. The simple consisted of 502 members of the academic community (professors and students). A survey was designed and the data was analysed with a significance level of 0.01, 4 degrees of freedom, and a critical value of 13,27. The data obtained were analyzed to determine if there were differences between entrepreneurial abilities among men and women. The most relevant findings include the existence of differences associated with the tendency among men to assume risks and in handling frustration. However, women perform better in the commercial capacity and in terms of self-esteem. It was concluded that women are better at communicating ideas and relating to others. It was also found that superior performance among the masculine population may be associated with cultural aspects stemming from the social functions that our culture attributes to men and women, and their different roles in the family.